If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2(2x + -8) = 5(2x + -7) + 7x Reorder the terms: 5x + -2(-8 + 2x) = 5(2x + -7) + 7x 5x + (-8 * -2 + 2x * -2) = 5(2x + -7) + 7x 5x + (16 + -4x) = 5(2x + -7) + 7x Reorder the terms: 16 + 5x + -4x = 5(2x + -7) + 7x Combine like terms: 5x + -4x = 1x 16 + 1x = 5(2x + -7) + 7x Reorder the terms: 16 + 1x = 5(-7 + 2x) + 7x 16 + 1x = (-7 * 5 + 2x * 5) + 7x 16 + 1x = (-35 + 10x) + 7x Combine like terms: 10x + 7x = 17x 16 + 1x = -35 + 17x Solving 16 + 1x = -35 + 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 16 + 1x + -17x = -35 + 17x + -17x Combine like terms: 1x + -17x = -16x 16 + -16x = -35 + 17x + -17x Combine like terms: 17x + -17x = 0 16 + -16x = -35 + 0 16 + -16x = -35 Add '-16' to each side of the equation. 16 + -16 + -16x = -35 + -16 Combine like terms: 16 + -16 = 0 0 + -16x = -35 + -16 -16x = -35 + -16 Combine like terms: -35 + -16 = -51 -16x = -51 Divide each side by '-16'. x = 3.1875 Simplifying x = 3.1875
| 0.5n=0.4+0.2n | | X+0.3x=100.00 | | -4b+9-7= | | 4x+5=5x-10 | | 8(x+3m+7)= | | -3(1+6r)=14+-r | | -4(x-4)+6=22 | | 12b-5c+5b+1= | | 16x+3y= | | 3[4+2(y-1)]=36 | | -4x+90=50 | | 7=5+2(7c+1) | | 4-12=5s+51 | | (50-2x)*x=200 | | (7+2)xX+1= | | 5x+61=73+2x | | -g=1.5g-3 | | m(x)=(3x-1)(3-x)+4x^3+19 | | y=(20+x)(3000-100x) | | -0.75x=0.86 | | (3-9x)= | | 3=4-3(5c-1) | | 20+10m=200 | | 5b-14-3b=30 | | 15-5x=26 | | 6x+7x=16 | | 2x-2=4(x-1) | | 9a+3a+12=36 | | -5+7(k+6)=93 | | 6(-p)=54 | | x^2+4x+2=5x+7 | | -2m+19= |